The Impact of Working Capital and Risk Management on Increasing Profitability at PT. Golden Titian Indonesia - Pirwansyah Pirwansyah; Darwin Kesuma; Mujari Mujari (Journal of Management, Economic, and Accounting, 2026)
This study aims to determine the effect of working capital on increasing profitability at PT. Golden Titian Indonesia. To determine the effect of risk management on increasing profitability at PT. Golden Titian Indonesia. To determine the effect of working capital and risk management on increasing profitability at PT. Golden Titian Indonesia. The analysis and discussion revealed that working capital significantly influences profitability at PT. Golden Titian Indonesia. Risk management has no significant effect on profitability at PT. Golden Titian Indonesia. Working capital and risk management simultaneously have a significant effect on profitability at PT. Golden Titian Indonesia.